Voodoo, vaccines and bed nets - Nik Stoop; Marijke Verpoorten; Koen Deconinck (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2017)
We provide the first quantitative analysis to scrutinize the ample ethnographic evidence that magico-religious beliefs affect the demand for conventional healthcare in Sub-Saharan Africa. We rely on the unique case of Benin, where Voodoo-adherence is freely reported, and varies greatly within villages and even within households, yet can be traced to historic events that are arguably exogenous to present-day healthcare behavior. These features allow us to account for confounding village- and household-factors, and address self-selection into Voodoo. We find that Voodoo adherence of the mother is associated with lower uptake of preventive healthcare measures and worse child health outcomes, a relationship that weakens but remains when controlling for village dummies and a large set of observables. We employ three different strategies to test for the potential influence of unobservables. The results suggest that the estimated Voodoo-effects are partly causal. A tentative exploration of the causal mechanisms suggests a mediating role of traditional healers.
Keywords: 330